2021
DOI: 10.1093/schbul/sbab105
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Pathologies in Schizophrenia-Spectrum Disorder—A Retrospective Chart Review

Abstract: Background The role of inflammatory processes in the etiology of schizophrenia is increasingly being investigated. A link between psychosis and inflammation measured with different biomarkers has been reported in the literature and needs to be further explored. To investigate the presence of inflammatory biomarkers in first-episode psychosis (FEP) we analyzed the largest available FEP cohort to date regarding routine CSF and blood diagnostics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…A meta-analysis indicated BBB leak in SZ, reflected by higher levels of CSF albumin [33 ▪▪ ]. Three subsequent studies corroborated this result and indicated BBB leakage across a relatively similar percentage of the patients (15.8% [52 ▪▪ ], 19% [53 ▪▪ ], 15% [34 ▪▪ ]). Reductions in the tight junction protein CLDN5 were reported in the hippocampus [43 ▪▪ ] and serum of the patients [42].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A meta-analysis indicated BBB leak in SZ, reflected by higher levels of CSF albumin [33 ▪▪ ]. Three subsequent studies corroborated this result and indicated BBB leakage across a relatively similar percentage of the patients (15.8% [52 ▪▪ ], 19% [53 ▪▪ ], 15% [34 ▪▪ ]). Reductions in the tight junction protein CLDN5 were reported in the hippocampus [43 ▪▪ ] and serum of the patients [42].…”
Section: Discussionmentioning
confidence: 85%
“…A group of first-episode SZ patients presented slightly increased systemic inflammation (41.4%, 116/280 SZ subjects), reflected by increased C-reac-tive protein levels in the blood, whereas signs of BBB leak were reported solely in 15.8% of the first-episode SZ patients (49/310 SZ), as reflected in higher CSF albumin [52 ▪▪ ]. In a cohort of 456 SZ patients, only 7% showed signs of neuroinflammation, although 19% of the SZ patients reported BBB leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Reference values were adjusted by age with the following formula: Qalb = (4 + age/15) × 10 -3 , age indicated as years (27). In accordance with other publications (12,28), OCBs were classi ed in ve pattern types as recommended by previous reports (29,30). The ve patterns are de ned as follows: pattern 1: normal CSF, pattern 2: multiple CSF restricted OCBs, pattern 3: identical OCBs in CSF and serum plus CSF restricted OCBs, pattern 4: identical OCBs in both CSF and serum, pattern 5: monoclonal bands in CSF and serum.…”
Section: Csf and Blood-based Vitamin Levelsmentioning
confidence: 92%
“…We therefore need innovative new methods to detect mild inflammation, as the current standard diagnostic procedures are inadequate. Peripheral inflammation might be informative as additional information for deciphering CNS inflammation, but often fail to correlate with CSF inflammation, as a recent study showed in patients with a schizophrenia-spectrum disorder ( 34 ). However, whether peripheral inflammation is useful is controversial, as another study showed upregulated complement mRNA expression in blood samples linked to cortical thinning in schizophrenia ( 35 ).…”
Section: Novel Discoveries In Methods Relevant For Immunopsychiatrymentioning
confidence: 99%